High Dietary Phosphate Exacerbates and Acts Independently of Low Autophagy Activity in Pathological Cardiac Remodeling and Dysfunction - Mingjun Shi; Sierra Shepard; Zhiyong Zhou; Jenny Maique; Olivia Seli; Orson W. Moe; Ming Chang Hu (Cells, 2021)
High phosphate contributes to uremic cardiomyopathy. Abnormal autophagy is associated with the development and progression of heart disease. What is unknown is the effects of phosphate on autophagy and whether the ill effects of phosphate on cardiomyocytes are mediated by low autophagy. High (2.0% w/w)-phosphate diet reduced LC3 puncta in cardiomyocytes and ratio of LC3 II/I and increased p62 protein, indicating that autophagy activity was suppressed. Mice with cardiomyocyte-specific deletion of autophagy-related protein 5 (H-atg5−/−) had reduced autophagy only in the heart, developed cardiac dysfunction with hypertrophy and fibrosis, and had a short lifespan. When H-atg5−/− mice were fed a high-phosphate diet, they developed more apoptosis in cardiomyocytes, more severe cardiac remodeling, and shorter lifespan than normal phosphate-fed H-atg5−/− mice, indicating that cardiac phosphotoxicity is imparted independently of atg5. In conclusion, although high phosphate suppresses autophagy, high phosphate and low autophagy independently trigger and additionally amplify cardiac remodeling and dysfunction.